2021
DOI: 10.2166/wst.2021.430
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the potential of biosynthesized zinc oxide nanoparticles for degradation of synthetic organic dyes as wastewater pollutants

Abstract: The azo dyes released into water from different industries are accumulating in the water bodies and bioaccumulating within living systems thereby affecting environmental health. This is a major concern in developing countries where stringent regulations are not followed for the discharge of industrial waste into water bodies. This has led to the accumulation of various pollutants including dyes. As these developing countries also face acute water shortages and due to the lack of cost-effective systems to remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 172 publications
0
9
0
Order By: Relevance
“…Next, the desired concentration of zinc nitrate, oxide, or sulfate is added to it, and the mixture is boiled. 52,53 At this point, we can also optimize the different conditions like temperature, pH, extract concentration, and incubation time. During the incubation period, drop-wise addition of sodium hydroxide is performed, which sometimes promotes the change of color of the mixture to yellow, which indicates visual confirmation of the synthesis of nanoparticles.…”
Section: Biogenic Approach For Nanoparticle Synthesismentioning
confidence: 99%
“…Next, the desired concentration of zinc nitrate, oxide, or sulfate is added to it, and the mixture is boiled. 52,53 At this point, we can also optimize the different conditions like temperature, pH, extract concentration, and incubation time. During the incubation period, drop-wise addition of sodium hydroxide is performed, which sometimes promotes the change of color of the mixture to yellow, which indicates visual confirmation of the synthesis of nanoparticles.…”
Section: Biogenic Approach For Nanoparticle Synthesismentioning
confidence: 99%
“…Nanoparticles have been utilized for the degradation of various anionic, catatonic, and neutral dyes [ 181 ]. Dyes, commonly used in paper, plastic, food, cosmetics, leather, textile, and pharmaceutical industries and have proven to be harmful to both aquatic and human life due to their toxic, mutagenic, carcinogenic, and teratogenic effects.…”
Section: Application Of Asteraceae -Based Nanopart...mentioning
confidence: 99%
“…The employment of nanoparticles in the photocatalysis process has come under scrutiny recently due to benefits such as their superior macroscopic-scale properties, high surfacevolume ratio and high surface energy. Recent studies on the biogenic nanoparticles have demonstrated that green synthesized metal oxide nanoparticles can effectively break down high molecular weight molecules and emerging pollutants without leaving harmful byproducts in the effluents [3,[7][8][9][10]. Recently, Batra et al [11] reported the review article on the efficient dye degradation strategies using green synthesized ZnO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%